2017
DOI: 10.1108/lht-11-2016-0122
|View full text |Cite
|
Sign up to set email alerts
|

RAMP – the Repository Analytics and Metrics Portal

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As such, while being easily accessible and commonly used, GA may not be the most appropriate tool to use in scientific research [18]. For example, prior research by OBrien et al [19] has demonstrated that 58% of activity on a website is unreported by GA.…”
Section: Monitoring Web Usagementioning
confidence: 99%
“…As such, while being easily accessible and commonly used, GA may not be the most appropriate tool to use in scientific research [18]. For example, prior research by OBrien et al [19] has demonstrated that 58% of activity on a website is unreported by GA.…”
Section: Monitoring Web Usagementioning
confidence: 99%
“…Only one respondent asked for statistics on individual users and it was not clear whether that was a statistic on a self-archiving researcher or a downloader of information. It would be interesting to compare IRUS with the RAMP system (Repository Analytics and Metrics Portal) in the US that seeks to measure and provide similar types of usage information (O'Brien, Arlitsch, Mixter, Wheeler, & Sterman, 2017;O'Brien et al, 2016).…”
Section: Metrics and Measurementmentioning
confidence: 99%
“…It is noteworthy that the same group of researchers are responsible for the Repository Analytics and Metrics Portal (RAMP) which seeks to improve the quality of usage and traffic analytics [19].…”
Section: Repository Visibility and Discovery: Related Workmentioning
confidence: 99%